PENYELESAIAN WANPRESTASI DALAM PERJANJIAN KREDIT PADA LEMBAGA PERKREDITAN DESA PADA DESA PAKRAMAN PADANGSAMBIAN DENPASAR - Ika Paramitha, A A Raka; Wiratni Darmadi, A A Sagung; Sukihana, Ida Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
Its business banking or other business entities are generally more emphasis on lending activities, as it can provide profit interest. Lending activities undertaken or banking institutions and other business entities are not purely lending capital to its customers, but it is complex include the sources of credit funds, allocation of funds, the organization and credit management, credit policy, loan documentation and administration, supervision credit, as well as the settlement of problem loans because of the bad faith of the customer (debtor), the denial of credit in the fulfillment of payment obligations (wanprestasi). Lending activities are conducted throughout the banking institutions, including other business entity called the Village Credit Institutions (hereinafter LPD) owned Pakraman village in Bali.
Keywords: Banking, Credit, Capital and Wanprestasi